Effects of applied mechanical stress on the properties of the boundary between circular domains in a cylindrical magnetic wire - Ján Ziman; Jozef Onufer; Peter Duranka; Mária Kladivová; Peter Vrábel (Physics Open)
The paper presents the study of the motion of an individual domain wall in a cylindrical amorphous wire with negative magnetostriction and helical anisotropy induced by the simultaneous application of torsional and tensile mechanical stresses. The non-zero axial component of the magnetization made it possible to monitor the motion of the domain wall by means of suitably wound pick-up coils. Experimental results showed that the wall mobility increases significantly with the application of torsional stress. For a model of a planar domain wall, the calculated eddy currents damping of the wall motion is too strong to explain this increase. Presence of a non-zero axial component of the magnetization can cause the transformation of a planar wall to a deformed wall, axial length of which increases with the applied torsion. It can be expected that the damping of the propagating deformed wall is lower and thus its mobility increases.